Bhutan : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This Selected Issues paper and Statistical Appendix on Bhutan underlie the macroeconomic impact of Tala, rapid private sector credit growth, and macroeconomic risks. In Bhutan, as the bulk of Tala-related flows go through the government accounts, this requires an appropriate fiscal stance and skillful expenditure management. Strong economic growth will require and lead to a deepening and further development of the financial system in Bhutan. The financial sector seems to be relatively shielded from adverse events, although risks remain.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet